ANALISIS KUALITAS PERAIRAN PANTAI SEBELUM DAN SESUDAH AKTIVITAS TRADISI BAU NYALE DI PANTAI SEGER KUTA LOMBOK TENGAH NTB - Rizal Ruliyas Arfian; Saimul Laili; Ahmad Syauqi (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2022)
Pollution is a problem for most of the territorial waters in Indonesia including the territorial waters on the coast of Seger Kuta, Central Lombok. One way to analyze the quality of waters in coastal areas is by analyzing water quality in the form of parameters, physics, chemistry, and biology. This method can provide information about the condition of a waters. The purpose of this study is to identify the condition of the quality of the waters of the Seger Coast before and after the Bau Nyale tradition based on physical, chemical and biological parameters. This research was conducted in February 2020 at three research stations and the results were compared with sea water quality standards based on the Minister of Environment Decree No. 51 of 2004 concerning Sea Water Quality Standards and other references. The results showed in general the quality of coastal waters before and after the Bau Nyale tradition at Seger Kuta beach, Central Lombok is still classified as good or lightly polluted waters. Plankton found in the study site before the Bau Nyale tradition there are 8 genera derived from 4 plankton groups namely Diatomae 5 genus, Dinophyceae 1 genus, Cynophiceae 1 genus and Cilliata 1 genus. The number of genera from each observation station before the Bau Nyale tradition ranged from 6-8 genera with a total abundance of 95-227, whereas after the Bau Nyale tradition there were 8 genera originating from 3 plankton groups, namely 6 genera Diatomae, 1 genus Mastigophora and 1 Cynophiceae . The number of genera from each station after the Nyale Odor tradition ranges from 7-8 genera with a total abundance of 62-171.